The reliability of an adolescent dietary pattern identified using reduced-rank regression: comparison of a FFQ and 3 d food record - Appannah, Geeta; Pot, Gerda Karolien; O'Sullivan, Therese Anne; Oddy, Wendy Hazel; Jebb, Susan Ann; Ambrosini, Gina Leslie (Cambridge University Press, 2014)
Despite the increasing use of dietary patterns (DP) to study diet and health outcomes, relatively few studies have examined the reliability of DP using different dietary assessment methods. Reduced-rank regression (RRR) is an emerging statistical method that incorporates a priori information to characterise DP related to specific outcomes of interest. The aim of the present study was to compare DP identified using the RRR method in a FFQ with those in a 3 d food record (FR). Participants were 783 adolescents from the Western Australian Pregnancy (Raine) Cohort Study who completed both a FFQ and FR at 14 years of age. A similar 'energy-dense, high-fat and low-fibre' DP was identified in the FFQ and FR that was characterised by high intakes of processed meat and sugar-sweetened beverages, and low intakes of vegetables and fresh fruit. Nutrient profiles for this DP were consistent in the FFQ and FR. Pearson's correlation coefficient between participants' z-scores for the DP identified in the FFQ and FR was 0·35 for girls and 0·49 for boys (P< 0·05). The mean difference between DP z-scores derived from the FFQ and FR was -0·08 (95 % CI -0·21, 0·04) for girls and -0·05 (95 % CI -0·17, 0·07) for boys. The 95 % limits of agreement were -2·55 to 2·39 for girls and -2·52 to 2·41 for boys. These findings suggest that very similar DP may be identified and their z-scores show modest agreement when applying the RRR method to dietary intake data collected from adolescents using a FFQ or FR.